The Integrity of Educated Millenial Generation in The Leadership Perspective - Khusnul Ashar; Axellina Muara Setyanti (Journal of International Conference Proceedings (JICP), 2022)
Leadership is an important part in all organizations and continues to be needed over time. Becoming a leader with integrity in the current and future generations of millennial society is a critical challenge. The millennial generation is generally characterized by increasing mastery of technology and increasing intensity of use of social media and the internet. On the other hand, there are four dimensions of integrity that a leader needs to master, namely the dimensions of honesty, responsibility, tolerance, and love for the homeland. A leader who has integrity will gain the trust of those he leads, because what he says is also his actions. In the era of the millennial generation, effective leadership will be realized if the leaders can meet the qualifications as visionary leaders and have intellectual abilities. But a good leader must also have dimensions of integrity. This study aims to observe the phenomenon of educated millennials in the perspective of leadership integrity through a literature study. This research contributes to providing an overview of how the educational environment can be a part in shaping the integrity of the educated millennial generation. Keywords: Educated Millennials, Integrity, Leadership.